The R2R3 MYB Transcription Factor MYB71 Regulates Abscisic Acid Response in Arabidopsis - Yuxin Cheng; Yanxing Ma; Na Zhang; Rao Lin; Yuan Yuan; Hainan Tian; Saddam Hussain; Siyu Chen; Wenting Yang; Ling Cai; Yingying Li; Xiaoping Wang; et al. (Plants, 2022)
Abscisic acid (ABA) regulates plant responses to abiotic stresses via regulating the expression of downstream genes, yet the functions of many ABA responsive genes remain unknown. We report here the characterization of MYB71, a R2R3 MYB transcription factor in regulating ABA responses in Arabidopsis. RT-PCR results show that the expression level of MYB71 was increased in response to ABA treatment. Arabidopsis protoplasts transfection results show that MYB71 was specifically localized in nucleus and it activated the Gal4:GUS reporter gene when recruited to the Gal4 promoter by a fused DNA binding domain GD. Roles of MYB71 in regulating plant response to ABA were analyzed by generating Arabidopsis transgenic plants overexpression MYB71 and gene edited mutants of MYB71. The results show that ABA sensitivity was increased in the transgenic plants overexpression MYB71, but decreased in the MYB71 mutants. By using a DEX inducible system, we further identified genes are likely regulated by MYB71, and found that they are enriched in biological process to environmental stimuli including abiotic stresses, suggesting that MYB71 may regulate plant response to abiotic stresses. Taken together, our results suggest that MYB71 is an ABA responsive gene, and MYB71 functions as a transcription activator and it positively regulates ABA response in Arabidopsis.